2018
DOI: 10.1111/bju.14538
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of a fast 1.5‐T biparametric with the 3.0‐T multiparametric ESUR magnetic resonance imaging protocol as a triage test for men at risk of prostate cancer

Abstract: Objective To compare prospectively the diagnostic performance of a biparametric (T2‐weighted imaging [T2WI] and diffusion‐weighted imaging [DWI]) 1.5‐T fast magnetic resonance imaging (fMRI) protocol with the standard 3.0‐T multiparametric MRI (mpMRI) protocol of the European Society of Urological Imaging (ESUR) in men referred for a prostate biopsy. Patients and Methods Ninety patients with a prostate cancer (PCa) risk of ≥10% according to the SWOP calculator 4 underwent first fMRI and then the reference mpMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
0
9
0
2
Order By: Relevance
“…Further studies reported promising results, although being affected by significant bias mainly concerning the MRI interpretation process (mpMRI and bpMRI read by the same radiologist during the same session) [85] and the reference standard (no biopsy result in men with negative MRI) [86]. The similar diagnostic performance of these two techniques was confirmed in other series [87][88][89] that attempted to better identify the eventual differences.…”
Section: Biparametric Mri Versus Mpmrimentioning
confidence: 80%
“…Further studies reported promising results, although being affected by significant bias mainly concerning the MRI interpretation process (mpMRI and bpMRI read by the same radiologist during the same session) [85] and the reference standard (no biopsy result in men with negative MRI) [86]. The similar diagnostic performance of these two techniques was confirmed in other series [87][88][89] that attempted to better identify the eventual differences.…”
Section: Biparametric Mri Versus Mpmrimentioning
confidence: 80%
“…Therefore, the authors conclude that bpMRI has the same diagnostic performance as mpMRI for the detection of PCa [29]. Recent single-center studies from 2018 published similar results [7, 9, 11, 12, 30].…”
Section: Diagnostic Performance Of Mpmri and Bpmrimentioning
confidence: 81%
“…Junker et al. reported a time reduction of 12 min using bpMRI [11] and another group found a time reduction of only 2.30 min [12]. A very fast biparametric MRI protocol that takes only 8.45 min has been published by Kuhl et al.…”
Section: Benefits Of Omitting Dcementioning
confidence: 99%
“…Bei Scannen der T2w-Bilder in 3 Ebenen mit zusätzlicher DWI dauert eine biparametrische MRT ca. 15 min [17,28]. Eine rezente Publikation berichtet über ein abgekürztes biparametrisches Protokoll, welches ca.…”
Section: Biparametrische Mrtunclassified
“…Die ESUR-Guidelines empfehlen für die Bildgebung Hochfeld-MRT, jedoch konnten Studien zeigen, dass zwischen Untersuchungen mit 1,5 bzw. 3 T kein Unterschied in der diagnostischen Genauigkeit bei der Anwendung von biparametrischen Protokollen besteht [28]. (.…”
Section: Biparametrische Mrtunclassified